Indoor concentrations of nitrogen dioxide and sulfur dioxide from burning solid fuels for cooking and heating in Yunnan Province, China. (6th October 2015) - Seow, W. J.; Downward, G. S.; Wei, H.; Rothman, N.; Reiss, B.; Xu, J.; Bassig, B. A.; Li, J.; He, J.; Hosgood, H. D.; Wu, G.; Chapman, R. S.; et al.
Abstract: The Chinese national pollution census has indicated that the domestic burning of solid fuels is an important contributor to nitrogen dioxide (NO2 ) and sulfur dioxide (SO2 ) emissions in China. To characterize indoor NO2 and SO2 air concentrations in relation to solid fuel use and stove ventilation in the rural counties of Xuanwei and Fuyuan, in Yunnan Province, China, which have among the highest lung cancer rates in the nation, a total of 163 participants in 30 selected villages were enrolled. Indoor 24‐h NO2 and SO2 samples were collected in each household over two consecutive days. Compared to smoky coal, smokeless coal use was associated with higher NO2 concentrations [geometric mean (GM) = 132 μ g/m 3 for smokeless coal and 111 μ g/m 3 for smoky coal, P = 0.065] and SO2 [limit of detection = 24 μ g/m 3 ; percentage detected (%Detect) = 86% for smokeless coal and 40% for smoky coal, P < 0.001]. Among smoky coal users, significant variation of NO2 and SO2 air concentrations was observed across different stove designs and smoky coal sources in both counties. Model construction indicated that the measurements of both pollutants were influenced by stove design. This exposure assessment study has identified high levels of NO2 and SO2 as a result of burning solid fuels for cooking and heating.